Transient absorption spectroscopic techniques for organic photovoltaics: Tracking the photogenerated charges - Sai Santosh Kumar, R.; Grancini, G.; Keivanidis, Panagiotis E.; Lanzani, G. (My University, 2012)
Here we present ultrafast transient absorption spectroscopy and cw-photoinduced absorption spectroscopy as useful tools for monitoring and investigating the photo-generated charges in organic molecule-based photovoltaics.